Chilean Rodeo as a National Symbol - A. V. Kutkova (Ибероамериканские тетради)
Rodeo is considered an important national symbol in Chile. The evolution of this cultural phenomenon throughout history reveals that it has not always enjoyed the recognition it has today. The first rodeos in Chile were held in the second half of the 16th century, but this word used to have a different meaning at the time. In the colonial era of Spanish America, «rodeo» referred to herding cattle (derived from the verb rodear meaning «to surround»), a hard and dangerous task in the vast expanses of the New World. Four centuries later, on January 10, 1962, the Chilean Olympic Committee officially recognized rodeo as a national sport that nowadays means a lot more to Chileans than a mere spectacle. Reflecting on how and why Chilean society, especially the intellectual elite, changed its attitude towards rural life helps to understand the fundamental characteristics of Chilean national identity. In the late 19th and early 20th century, when Chilean society sought national self-determination, criollista writers turned their attention to rural life and found that the huaso rider, the protagonist of the rodeo, embodied Chilean ethnotypic spirit. The idealized image of the Chilean cowboy, born on the pages of books and immortalized in early 20th-century cinema, resonated with different strata of society. Today rodeo, which used to be a key element of everyday life in Central Chile, has become part of the entire country’s intangible cultural heritage and a significant symbol of the Chilean nation, which began to take shape in times of the Conquest.